Pengaruh Kinerja Keuangan Terhadap Harga Saham (Studi Pada Perusahaan Mining Industry di BEI) - Radiasi Alam (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2018)
This study attempts to measure the ability of financial performance ratios in influencing stock prices. Ratios consisting of aspects of liquidity, solvency, and profitability activities include the current ratio, quick ratio, total asset turnover, inventory turnover, debt equity ratio and return on equity. Sample was 22 companies listed mining industry in Indonesia Stock Exchange in the 2007–2017 timeframe. Sample observations are compiled using the data pooled by combining time series and cross section. Multiple Linear Regression Analysis is used to determine the effect of independent variables on stock prices, then the results of the regression analysis showed negative effect on the current ratio of stock price although not significantly so the first hypothesis is rejected. Quick ratio, total asset turnover and inventory turnover has a positive effect on stock prices but not significant, while the debt-equity ratio and a significant negative effect on stock prices. Return on equity positive and significant effect on stock prices. The coefficient of determination showed only 44.1% of independent variables can explain the variation in stock prices, so further research is needed to explore other financial performance ratios that can affect stock price mining industry sector.